THE INFLUENCE OF WORK-LIFE BALANCE ON FAMILY CONFLICT IN SINGLE PARENTS IN JELBUK, JEMBER - Dwi Cahyadi, Teguh; Haikal Ali Basyarahil, Muhammad; Sabdo Djati P S, Syailendra (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Work-life balance (WLB) is an individual's ability to balance the demands of work and personal life. For single parents, this balance is a big challenge considering that they have to carry out the dual role of being the breadwinner as well as the main caregiver in the family. The imbalance between work and personal life often triggers stress that has an impact on family conflict. This study aims to analyze the influence of work-life balance on family conflict in single parents in Jelbuk District, Jember. This study used a quantitative approach with a correlational design to measure the relationship between work-life balance (Variable X) and family conflict (Variable Y). The study population consisted of single parents who have lived as single parents for at least two years. The sampling technique used stratified random sampling, with 10% of respondents taken from each age category of single parents. Data collection was conducted through interviews, observation, documentation, and questionnaires. The results of the study are expected to provide scientific insight into how work-life balance affects conflict in single-parent families. The findings are also expected to be a reference for intervention programs that support the improvement of family welfare through strengthening work-life balance in single parents.